High-Throughput Qualitative and Quantitative Drug Checking by MALDI HRMS - Joye, Timothée; Widmer, Christèle; Morger Mégevand, Roxane; Longère, Serge; Augsburger, Marc; Thomas, Aurélien (Frontiers in Chemistry, 2020)
Illicit drugs are a global health problem, since both their acute and chronic consumption have negative impacts on the drug user’s health. Allowing the drug users to chemically analyse their product prior consumption to assess the presence of adulterants or other non-expected substances, drug checking facilities are receiving a growing interest. Such harm reduction programs allow to reduce the risks associated with drug consumption without encouraging it. In particular, the emergence of new psychoactive substances (NPS) emphasizes the risk for the population increasing the diversity and the lability of illicit drugs on the market. Analytical developments are required to catch up with this rapid evolution and reduce the potential harm caused by such consumption. In this study, we developed a matrix-assisted laser desorption/ionization (MALDI) high-resolution mass spectrometry (HRMS) strategy for the high-throughput qualitative and quantitative analysis of drug checking samples. The use of online-based m/z cloud library for untargeted compound search improved the ability to identify unknown compounds. Sixty-seven drug checking samples were analysed using this analytical strategy allowing the detection of 10 designer drugs and several classical drugs of abuse (mainly cocaine and MDMA) as well as adulterants and contaminants. The results were then compared with routine analyses of the same samples using conventional approaches showing similar performance while removing the use of chromatographic separation thus resulting in a significant reduction of the time required for sample preparation and analysis. This study enlightens the potential of MALDI-HRMS as a high-throughput approach allowing to speed-up up to 6 times the identification and quantification of substances enabling to catch the fast changes on the drug of abuse market. This strategy could be an interesting alternative analytical approach allowing better prevention and harm reduction for drug users.